Infarct size-limiting effect of epoxyeicosatrienoic acid analog EET-B is mediated by hypoxia-inducible factor-1α via downregulation of prolyl hydroxylase 3 - Neckář, Jan; Hsu, Anna; Hye Khan, Md Abdul; Gross, Garrett J; Nithipatikom, Kasem; Cyprová, Michaela; Benák, Daniel; Hlaváčková, Markéta; Sotáková-Kašparová, Dita; Falck, John R; Sedmera, David; Kolář, František; et al. (American journal of physiology. Heart and circulatory physiology, 2018)
Epoxyeicosatrienoic acids (EETs) decrease cardiac ischemia-reperfusion injury; however, the mechanism of their protective effect remains elusive. Here, we investigated the cardioprotective action of a novel EET analog, EET-B, in reperfusion and the role of hypoxia-inducible factor (HIF)-1α in such action of EET-B. Adult male rats were subjected to 30 min of left coronary artery occlusion followed by 2 h of reperfusion. Administration of 14,15-EET (2.5 mg/kg) or EET-B (2.5 mg/kg) 5 min before reperfusion reduced infarct size expressed as a percentage of the area at risk from 64.3 ± 1.3% in control to 42.6 ± 1.9% and 46.0 ± 1.6%, respectively, and their coadministration did not provide any stronger effect. The 14,15-EET antagonist 14,15-epoxyeicosa-5( Z)-enoic acid (2.5 mg/kg) inhibited the infarct size-limiting effect of EET-B (62.5 ± 1.1%). Similarly, the HIF-1α inhibitors 2-methoxyestradiol (2.5 mg/kg) and acriflavine (2 mg/kg) completely abolished the cardioprotective effect of EET-B. In a separate set of experiments, the immunoreactivity of HIF-1α and its degrading enzyme prolyl hydroxylase domain protein 3 (PHD3) were analyzed in the ischemic areas and nonischemic septa. At the end of ischemia, the HIF-1α immunogenic signal markedly increased in the ischemic area compared with the septum (10.31 ± 0.78% vs. 0.34 ± 0.08%). After 20 min and 2 h of reperfusion, HIF-1α immunoreactivity decreased to 2.40 ± 0.48% and 1.85 ± 0.43%, respectively, in the controls. EET-B blunted the decrease of HIF-1α immunoreactivity (7.80 ± 0.69% and 6.44 ± 1.37%, respectively) and significantly reduced PHD3 immunogenic signal in ischemic tissue after reperfusion. In conclusion, EET-B provides an infarct size-limiting effect at reperfusion that is mediated by HIF-1α and downregulation of its degrading enzyme PHD3. NEW & NOTEWORTHY The present study shows that EET-B is an effective agonistic 14,15-epoxyeicosatrienoic acid analog, and its administration before reperfusion markedly reduced myocardial infarction in rats. Most importantly, we demonstrate that increased hypoxia-inducible factor-1α levels play a role in cardioprotection mediated by EET-B in reperfusion likely by mechanisms including downregulation of the hypoxia-inducible factor -1α-degrading enzyme prolyl hydroxylase domain protein 3.
Keywords: heart; signální transdukce; Hypoxia-Inducible Factor-Proline Dioxygenases; Signal Transduction; hypoxia-inducible factor-1α; 8,11,14-Eicosatrienoic Acid; funkce levé komory srdeční; Proteolysis; Ventricular Remodeling; Down-Regulation; reperfuzní poškození myokardu; kyselina 8,11,14-eikosatrienová; prolyl-4-hydroxylasy HIF; zvířata; infarkt myokardu; Hypoxia-Inducible Factor 1, alpha Subunit; Myocardial Reperfusion Injury; prolyl hydroxylase 3; down regulace; proteolýza; epoxyeicosatrienoic acid; faktor 1 indukovatelný hypoxií - podjednotka alfa; potkani Sprague-Dawley; Male; Myocardial Infarction; ischemia-reperfusion; myokard; Rats, Sprague-Dawley; Animals; Myocardium; mužské pohlaví; Disease Models, Animal; remodelace komor; Ventricular Function, Left; modely nemocí na zvířatech